(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The lives of Jews have always been a challenging one. Be it history or legends, all carry tales of Jewish suffering and anxiety. Philip Roth is a prominent Jewish writer whose writings are generally pertaining to Jewish anxiety and their longing to assimilate with the larger society. This article shall analyse such struggles of Jews with reference to some of the novels of Philip Roth. The history of Jews and their sensibilities will also be included in the study.